2013
DOI: 10.1124/mol.113.089292
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Regulates Expression ofμ-Opioid Receptor MOR-1A, an Intron-Retention Carboxyl Terminal Splice Variant of theμ-Opioid Receptor (OPRM1) Gene via miR-103/miR-107

Abstract: The m-opioid receptor (MOR-1) gene OPRM1 undergoes extensive alternative splicing, generating an array of splice variants. Of these variants, MOR-1A, an intron-retention carboxyl terminal splice variant identical to MOR-1 except for the terminal intracellular tail encoded by exon 3b, is quite abundant and conserved from rodent to humans. Increasing evidence indicates that miroRNAs (miRNAs) regulate MOR-1 expression and that m agonists such as morphine modulate miRNA expression. However, little is known about m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 65 publications
2
52
0
Order By: Relevance
“…31 In addition, opioid tolerance developed in these mice after insertion of morphine pellets, consistent with studies that showed chronic opioid administration led to opioid tolerance via mu-opioid receptor downregulation on neurons. 14,27 Our finding that these 2 collective mechanisms, persistent pain and chronic opioid administration, lead to mu-opioid receptor downregulation on neurons in our mouse model is consistent with previous studies demonstrating that these are 2 well known mechanisms of mu-opioid receptor downregulation. 17 We attempted to reverse the effect of mu-opioid receptor downregulation through adenoviral gene therapy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…31 In addition, opioid tolerance developed in these mice after insertion of morphine pellets, consistent with studies that showed chronic opioid administration led to opioid tolerance via mu-opioid receptor downregulation on neurons. 14,27 Our finding that these 2 collective mechanisms, persistent pain and chronic opioid administration, lead to mu-opioid receptor downregulation on neurons in our mouse model is consistent with previous studies demonstrating that these are 2 well known mechanisms of mu-opioid receptor downregulation. 17 We attempted to reverse the effect of mu-opioid receptor downregulation through adenoviral gene therapy.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was consistent with our previous publication 31 in which we showed that although cancer pain tends to dampen mu-opioid receptor expression on the associated sensory neurons, mu-opioid receptor expression in these neurons is maintained in the presence of cancers that are transduced with Ad-OPRM1 to re-express mu-opioid receptors. Furthermore, we showed that morphine treatment, which was generally thought to dampen mu-opioid receptor expression in central nervous system tissue, 14 did not dampen mu-opioid receptor expression in neurons from mice transduced with Ad-OPRM1. In other words, Ad-OPRM1 treatment rescued mu-opioid expression on neurons.…”
Section: Resultsmentioning
confidence: 85%
“…miR-181a-5p was found to be upregulated by morphine treatment in mouse hippocampal progenitor cell lineages, suggesting its potential role in neurogenesis [26] and drug addiction [27]. miR-103a-3p was also reported to be upregulated following chronic exposure to morphine, which is known to downregulate MOR [28]. On the other hand, oxycodone treatment resulted in the upregulation of two miRNAs, namely, miR-339-3p and miR-23a-3p (Table 1), and miR-339-3p was reported to inhibit MOR function [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MOR-1 (exon 1), MOR-1A, MOR-1X, and MOR-1K splice variants appear to differ across CNS cell types (Dever et al, 2012; Dever et al, 2014). Evolving evidence suggests that there are significant functional differences among MOR splice variants (Pan et al, 2005; Majumdar et al, 2011; Dever et al, 2012; Xu et al, 2014; Lu, Xu, Xu, Pasternak, & Pan, 2014). Thus far, the findings are limited to neural cells isolated from a relative small number of individuals, and from imprecisely defined brain regions.…”
Section: Genetic Factors That Modulate Hiv-1 Infectivity and Neuromentioning
confidence: 99%